Prospective Evaluation of Results of Surgical Treatment of Patients with Idiopathic Macular Hole by Phacovitrectomy and Combined Cataract and Vitrectomy Surgery - Kinga Tochman-Kanty; Monika Jasielska; Jerzy Mackiewicz (Okulistyka)
Purpose of the study: The purpose of the study was to compare the morphological and functional results of the studied patients with idiopathic macular hole treated with a one-stage method (phacovitrectomy) and combined cataract and vitrectomy surgery.